Gene expression profiling in pure neural leprosy: insights into pathogenesis and diagnostic biomarkers - de Athaide, Mariana Martins; Leal-Calvo, Thyago; Da Silva, Tatiana Pereira; Rosa, Thabatta Leal Silveira Andrezo; Ferreira, Helen; Pascarelli, Bernardo Miguel de Oliveira; Siquara de Sousa, Ana Caroline; Jardim, Marcia Rodrigues; Pinheiro, Roberta Olmo (Frontiers in Immunology, 2025)
IntroductionLeprosy may affect skin and nerves, leading to permanent disabilities and deformities. Pure neural leprosy (PNL) lacks skin lesions, complicating diagnosis. Moreover there is no a specific treatment to control neural damage. Transcriptomic profiling may reveals unique gene expression changes in PNL nerves, shedding light on immune response and pathogenesis. These findings may guide early diagnosis and improve patient outcome.MethodsIn the present study, we investigated the gene profiling of nerve samples from patients with PNL and revealed significant transcriptomic alterations compared to non-leprosy controls.ResultsPrincipal Component Analysis (PCA) of the 500 most differentially expressed genes separated the groups, with 1,199 genes showing differential expression (|log2FC| ≥ 1, FDR ≤ 0.1). Downregulated genes included GAS2L2, TRIM67, IL1RAPL1, MAP1LC3B2, and NTNG1, implicated in neuronal development and autophagy, while upregulated genes were linked to immune responses. Functional analyses highlighted inflammasome activation and autophagy impairment in PNL, correlating with nerve inflammation and architecture loss.DiscussionWe hope that our data will aid in identifying new markers, fostering strategies for early diagnosis, preventing disabilities, and improving the management of PNL patients.